2018
DOI: 10.1017/gmh.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Community cognitive interviewing to inform local adaptations of an e-mental health intervention in Lebanon

Abstract: Background.Lebanon has a need for innovative approaches to increase access to mental health care to meet the country's current high demand. E-mental health has been included in its national mental health strategy while in parallel the World Health Organization has produced an online intervention called ‘Step-by-Step’ to treat symptoms of depression that is being tested in Lebanon over the coming years.Aim.The primary aim of this study is to conduct bottom-up, community-driven qualitative cognitive interviewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 20 publications
6
83
0
1
Order By: Relevance
“…However, the single randomized control trial included in the present study found a statistically significant reduction in post-traumatic stress syndrome symptoms in Arab patients from war-torn backgrounds [34]. Additionally, the remainder of the articles showed efficacy of the technologies as screening tools for this population [6,[28][29][30][31][32][33][34][35][36]. It is imperative that mMHealth innovations are compatible with local needs of intended adopters and implementing institutions.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the single randomized control trial included in the present study found a statistically significant reduction in post-traumatic stress syndrome symptoms in Arab patients from war-torn backgrounds [34]. Additionally, the remainder of the articles showed efficacy of the technologies as screening tools for this population [6,[28][29][30][31][32][33][34][35][36]. It is imperative that mMHealth innovations are compatible with local needs of intended adopters and implementing institutions.…”
Section: Discussionmentioning
confidence: 58%
“…Barriers discussed primarily included primarily cultural, financial, technical, infrastructural and data privacy limitations and lack of mental health awareness in the study populations. Results and key findings are tabulated in Table 3 [6,[28][29][30][31][32][33][34][35][36]. They preferred telepsychiatry in their mother tongue rather than interpreter-assisted care.…”
Section: Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of cultural and contextual adaptation of Step-by-Step in Lebanon is described in Abi Ramia et al (2018). This process followed an (unpublished) WHO draft protocol for cultural adaptation and included several steps.…”
Section: Lebanonmentioning
confidence: 99%
“…Qualitative Befragungen mit verschiedenen kulturellen Gruppen, z. B. der lokalen Bevölkerung, syrischen und palästinensischen Geflüchteten, Vertretern religiöser Gruppen und Fachkräften aus der primären Gesundheitsversorgung, zeigen, dass eine Intervention wie Step-by-Step begrüßt und als sinnvoll erachtet wird [8]. Das Gesundheitsministerium sieht Step-by-Step als ersten Schritt in einem Stepped-Care-Modell.…”
Section: Mobile Selbsthilfe -Schritt Für Schrittunclassified